1998
DOI: 10.1097/00007890-199802150-00002
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation Tolerance Prevents Cardiac Allograft Vasculopathy in Major Histocompatibility Complex Class I-Disparate Miniature Swine1

Abstract: These findings in a preclinical system establish the significance of antigen-dependent mechanisms in the pathogenesis of CAV and underscore the importance of achieving tolerance in clinical transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
88
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(94 citation statements)
references
References 34 publications
5
88
1
Order By: Relevance
“…Thus, vascularized grafts are relatively tolerogenic (21,25,26), whereas skin and tissue grafts are relatively immunogenic, probably because they release cells or Ags from cells into the lymphatic system where they sensitize the host (27). Even in the case of autografts, direct thymic grafts require a revascularization period after transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, vascularized grafts are relatively tolerogenic (21,25,26), whereas skin and tissue grafts are relatively immunogenic, probably because they release cells or Ags from cells into the lymphatic system where they sensitize the host (27). Even in the case of autografts, direct thymic grafts require a revascularization period after transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…Given the rapid rejection of near-syngeneic grafts we were surprised that no rejection occurred in IFN-γ perfused, MHC class I mismatched heart grafts of heart-kidney recipients. According to historical experiments, transplantation of a MHC class I disparate kidney combined with a 12-day course of high-dose CyA induces stable tolerance not only to the kidney but also to the cotransplanted heart (6). Studies investigating the mechanism of tolerance in this model revealed regulatory T cells (8) and upregulation of interleukin (IL) 10 (9) in tolerant heart-kidney recipients.…”
Section: Discussionmentioning
confidence: 99%
“…In Group 2 transplants were performed between highly inbred animals (G8; co-ancestry > 0.92) (5) referred to as nearsyngeneic. Group 3 recipients were cotransplanted with a MHC class I disparate heart and kidney, which uniformly induces tolerance to both grafts (6). An additional group of animals received intracoronary IFN-γ infusion into their native hearts.…”
Section: Methodsmentioning
confidence: 99%
“…More recently, it was shown, in different experimental models, that specific tolerance can be induced following the reconstitution of the host bone marrow with genetically modified host hematopoietic cells engineered to express donor MHC genes. 83,84 Another interesting approach to induce donor-specific tolerance has been attempted by intrathymic injection of autologous cells engineered to express donor MHC. Knechtle et al 85 reported donor-specific unresponsiveness to MHC-disparate liver and cardiac transplants when autologous myoblasts and myotubes were engineered to express donor class I MHC.…”
Section: Inhibition Of Leukocyte-mediated Rejectionmentioning
confidence: 99%